Infused-liquid-switchable porous nanofibrous membranes for multiphase liquid separation - Yang Wang (Nature Portfolio, 2017)
Separating immiscible liquids with small surface energy differences remains a challenge. Here, the authors develop a polarity-based strategy for the separation of multiphase mixtures of immiscible liquids, even those with surface energy differences as small as 2 mJ m-2.